Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26020416
|View full text |Cite
|
Sign up to set email alerts
|

Muscari comosum L. Bulb Extracts Modulate Oxidative Stress and Redox Signaling in HepG2 Cells

Abstract: Muscari comosum L. bulbs are commonly used as food in South Italy and also in folk medicine. By evaluating in vitro antioxidant activity and biological activities of their aqueous and methanol extracts, we shed light on the potential role, including both the nutraceutical and health benefits, of this plant. Total polyphenol content (TPC) and total flavonoid content (TFC) were evaluated by the Folin–Ciocalteu method and by the aluminum chloride method, respectively. Antioxidant activity was investigated by thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the cell line study, the antioxidant activities of LC bulb extracts were evaluated by measuring intracellular reactive oxygen species stimulated through tert-butyl hydroperoxide (t-BOOH) and expression of antioxidant-related genes in the HepG2 cells. Pretreatment with extract at low doses decreased the production of ROS, which had been enhanced due to the t-BOOH treatment in the HepG2 cells [ 33 ]. Additionally, expression of several genes/markers related with antioxidant activities, such as nuclear factor-erythroid 2 p45-related factor 2 ( NRF2 ), superoxide dismutase ( SOD-2 ), glutathione peroxidase ( GPX1 ), catalase ( CAT ), NADPH quinone oxidase-1 ( NQO1 ), ATP binding cassette subfamily C member ( ABCC6 ), and ATP binding cassette subfamily G member ( ABCG2 ) were studied through RT-PCR experiments.…”
Section: Bioactivitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cell line study, the antioxidant activities of LC bulb extracts were evaluated by measuring intracellular reactive oxygen species stimulated through tert-butyl hydroperoxide (t-BOOH) and expression of antioxidant-related genes in the HepG2 cells. Pretreatment with extract at low doses decreased the production of ROS, which had been enhanced due to the t-BOOH treatment in the HepG2 cells [ 33 ]. Additionally, expression of several genes/markers related with antioxidant activities, such as nuclear factor-erythroid 2 p45-related factor 2 ( NRF2 ), superoxide dismutase ( SOD-2 ), glutathione peroxidase ( GPX1 ), catalase ( CAT ), NADPH quinone oxidase-1 ( NQO1 ), ATP binding cassette subfamily C member ( ABCC6 ), and ATP binding cassette subfamily G member ( ABCG2 ) were studied through RT-PCR experiments.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…Recently, aqueous and methanolic (50 and 70%) extracts of LC bulbs were used to study the total phenolic and flavonoid contents before the evaluation of their biological properties. The maximum phenolic and flavonoid contents were found to be present in the 70% methanolic extract, i.e., 58.72 mgGAE/g and 20.37 mg QE/g, respectively [33]. a Peak area relative to total peak area percentage (relative area percentage); NP: not provided).…”
Section: Phytochemicals Reported In Lcmentioning
confidence: 99%
“…Biological systems include a number of antioxidant enzymes involved in the reduction of ROS. Phenols have been reported to increase the expression of body defense enzymes like catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD) [15,37]. For this reason, it was decided to test the effect of the Lucanian S. aethiopicum peel extract on the expression of different antioxidant enzymes.…”
Section: Effect Of S Aethiopicum Peel Extract On Antioxidant Defense ...mentioning
confidence: 99%
“…(SOD) [15,37]. For this reason, it was decided to test the effect of the Lucanian S. aethiopicum peel extract on the expression of different antioxidant enzymes.…”
Section: Effect Of S Aethiopicum Peel Extract On Antioxidant Defense ...mentioning
confidence: 99%
“…The food and medicinal use of the bulb is ancient, and its excellent properties were known by the Egyptians, the Greeks, and all the other inhabitants of the Mediterranean area and Asia Minor [2,3]. In particular, in Turkey [4] and in Italian regions as Sardinia [5], Sicily [6], Basilicata [3,7], Puglia [8], Campania, Molise, and Calabria [9], the bulb is used in traditional gastronomy due to its characteristic strong bitter taste [2,10] and interesting biological activities such as anti-inflammatory, anti-cancer, anti-hyperglycemic, diuretic, aphrodisiac, and antioxidant effects [9][10][11]. Recently, some authors have reported the antiobesity effects of raw bulbs due to their high total polyphenol and flavonoid content [9].…”
Section: Introductionmentioning
confidence: 99%